2020
DOI: 10.3390/diseases8020008
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Weight Cycling and Central Fat Distribution in Females With Obesity: A Brief Report

Abstract: Weight cycling (WC) is a common phenomenon in patients with obesity, however, its consequence on body composition has not yet been fully understood. Therefore, we aimed to determine whether multiple WC can negatively affect the latter, especially in terms of body fat distribution in female adults seeking treatment that are overweight or obese. Body composition was obtained using a segmental body composition analyser (MC-780MA, Tanita Corp., Tokyo, Japan) in 125 adult females who had been referred to the Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Unfortunately, the data available suggest that approximately 80% of participants who achieve weight loss will experience approximately 50% weight regain within one year following the end of the intervention (13)(14)(15)(16). Regular physical activity participation and reduced energy and fat intake are important for long-term weight maintenance, influencing the relationship between postintervention weight regain and adverse health outcomes (17)(18)(19). The Women's Health Initiative Observational Study reported associations between weight gain and weight cycling (intentional weight loss and subsequent weight regain) with an increase in postmenopausal breast and endometrial cancer risk (20).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the data available suggest that approximately 80% of participants who achieve weight loss will experience approximately 50% weight regain within one year following the end of the intervention (13)(14)(15)(16). Regular physical activity participation and reduced energy and fat intake are important for long-term weight maintenance, influencing the relationship between postintervention weight regain and adverse health outcomes (17)(18)(19). The Women's Health Initiative Observational Study reported associations between weight gain and weight cycling (intentional weight loss and subsequent weight regain) with an increase in postmenopausal breast and endometrial cancer risk (20).…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, a study in 2020 of 125 women living with obesity found that self-reported weight cycling was associated with an increase in FM of about 4 kg. 25 Our study using objectively measured weight trajectories over 24 months adds to these self-reported studies and collectively challenges the hypothesis that the preferential preservation or recovery of FM with weight cycling is less applicable to those with overweight or obesity. Conventionally, the impact on FM and FFM with weight cycling has been explained by the 'fat overshoot' theory, based on the concept that the suppression of thermogenesis observed with energy restriction persists during weight regain, prioritizing the recovery of FM.…”
Section: Discussionmentioning
confidence: 72%
“…This study has notable strengths. In particular, the objective measure of FM and FFM over repeated annual cycles in a sample that was large enough to categorize into seven different weight loss and weight gain trajectories adds to previous smaller studies in those with overweight and obesity that have relied on self‐reported, or the generation of fewer categories meaning different trajectories were combined 23–25 . However, there are also limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-frequency segmental body composition analyzer (MC-780MA, Tanita Corp., Tokyo, Japan) was used to measure body composition based on three frequencies providing highly accurate, whole-body, and segmental measurements [25]. Participant age, gender, and height information were entered into the device [25]. Then, the participant was instructed to stand in a stable, barefoot position.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Separate readings for different body segment compositions were obtained. These readings were based on an algorithm incorporating impedance, age, and height to estimate total BF, fat-free mass (FFM), and total body water (TBW) [25].…”
Section: Anthropometric Measurementsmentioning
confidence: 99%